Nanobody-Dependent Delocalization of Endocytic Machinery in Arabidopsis Root Cells Dampens Their Internalization Capacity - Winkler, Joanna; De Meyer, Andreas; Mylle, Evelien; Storme, Veronique; Grones, Peter; Van Damme, Daniël (Frontiers in Plant Science, 2021)
Plant cells perceive and adapt to an ever-changing environment by modifying their plasma membrane (PM) proteome. Whereas secretion deposits new integral membrane proteins, internalization by endocytosis removes membrane proteins and associated ligands, largely with the aid of adaptor protein complexes and the scaffolding molecule clathrin. Two adaptor protein complexes function in clathrin-mediated endocytosis at the PM in plant cells, the heterotetrameric Adaptor Protein 2 (AP-2) complex and the octameric TPLATE complex (TPC). Whereas single subunit mutants in AP-2 develop into viable plants, genetic mutation of a single TPC subunit causes fully penetrant male sterility and silencing single subunits leads to seedling lethality. To address TPC function in somatic root cells, while minimizing indirect effects on plant growth, we employed nanobody-dependent delocalization of a functional, GFP-tagged TPC subunit, TML, in its respective homozygous genetic mutant background. In order to decrease the amount of functional TPC at the PM, we targeted our nanobody construct to the mitochondria and fused it to TagBFP2 to visualize it independently of its bait. We furthermore limited the effect of our delocalization to those tissues that are easily accessible for live-cell imaging by expressing it from the PIN2 promotor, which is active in root epidermal and cortex cells. With this approach, we successfully delocalized TML from the PM. Moreover, we also show co-recruitment of TML-GFP and AP2A1-TagRFP to the mitochondria, suggesting that our approach delocalized complexes, rather than individual adaptor complex subunits. In line with the specific expression domain, we only observed minor effects on root growth, yet realized a clear reduction of endocytic flux in epidermal root cells. Nanobody-dependent delocalization in plants, here exemplified using a TPC subunit, has the potential to be widely applicable to achieve specific loss-of-function analysis of otherwise lethal mutants.